-8-4a-9=8a+6

Simple and best practice solution for -8-4a-9=8a+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-4a-9=8a+6 equation:



-8-4a-9=8a+6
We move all terms to the left:
-8-4a-9-(8a+6)=0
We add all the numbers together, and all the variables
-4a-(8a+6)-17=0
We get rid of parentheses
-4a-8a-6-17=0
We add all the numbers together, and all the variables
-12a-23=0
We move all terms containing a to the left, all other terms to the right
-12a=23
a=23/-12
a=-1+11/12

See similar equations:

| g-1/7=0.9 | | 2x-3-3x-5=10 | | 4(3−1)x=4 | | 27=46+2x+2 | | Xx2+5=34 | | 2x-3-3x-5=0 | | 2x-2+2x-9=13 | | -3=12x+35-10x | | -6+8(-2p-1)=82 | | 5(2x+1)-2(x-4)=-3 | | 13y+5=9y+27 | | 12x-3=17 | | (f-8)12=84 | | 3x=x-102 | | 2X5,+12=4x | | 30/4x=-6 | | y-3=21 | | 3w-5=-2w+10 | | 4(2z-18)=18 | | 2x+50=340 | | 3-x=15 | | 10m-8=-6-(2-5m) | | 36x=28 | | |5a+9|=|6a-5| | | 7q+3q−6=4 | | 6(3+e)=42 | | 2(x+2)+3(x-3)=20 | | 36x=26 | | 3x+5=x+2(x-4) | | 5x+2(5x+3)=15x | | x+10=22 | | 5(x+3)=2(2x+1)-2(3x-1)+3(2x+1) |

Equations solver categories